PENGARUH MODEL PEMBELAJARANKOOPERATIF TIPE SNOWBALL THROWING TERHADAP HASIL BELAJAR IPA - Agus Prasetyo; Hidayati Hidayati; Astuti Wijayanti (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2015)
The descriptive research aims to understand a tendency of study science outcomes in student of class VIII Banguntapan 2 Junior High School in 2015/2016. This research uses cooperative which is type of Snowball Throwing and expository model. The comparative research aims to understand a difference of study science outcomes in student of class VIII Banguntapan 2 Junior High School in 2015/2016 with uses cooperative of Snowball Throwing and Expository model. This method of research is a Quasy Experiment. The result of descriptive research is to show a tendency of science study outcomes in student of class VIII Banguntapan 2 Junior High School in 2015/2016 which uses Snowball Throwing is the highest category than Expository model. Then, the result of comparative research, there is difference of science study outcomes in student of class VIII Banguntapan 2 Junior High School which uses Snowball Throwing and Expository model. So that there is an influence in a cooperative which is type of Snowball Throwing toward a science study outcomes in student of VIII Banguntapan 2 Junior High School in 2015/2016.